Septic Thrombophlebitis in The Upper Limb Secondary to Folliculitis in The Hand (Revista de Medicina Clinica, 2023)
Deep vein thrombosis of the upper extremities is a rare disease and that does not mean we can forget about it, since it can cause important complications such as septic thrombophlebitis. We present the case of a 54-year-old patient with an initial pustular lesion in the right hand of 15 days of evolution, appearing in the last 3 days inflammation and pain, from the wrist to the axillary region, following the venous path of the arm, being compatible with a thrombophlebitis and confirmed with Doppler ultrasound. Empirical intravenous antibiotic therapy and anticoagulation with heparin were initiated, presenting clinical improvement. However, 3 days later, small, non-suppurative nodular lesions appeared following the venous course. The patient was discharged with oral antibiotic therapy and anticoagulation with heparin. In the first review, after observing a new nodular lesion with persistent phlebitic cord, antibiotic therapy was restarted for a week. After that, the nodules on her forearm had practically resolved, but those on her wrist and arm fluctuated, drained, obtaining negative cultures. In the subsequent review, the nodular lesions had been filled again, and due to elevated acute phase reactants, the patient was readmitted, undergoing new drainage and intravenous antibiotic therapy. In control Doppler ultrasound, thrombophlebitis persists, maintaining heparin. The patient showed clinical improvement, so she was discharged to her home to continue oral antibiotic therapy for 7 days and then discontinued, resulting in remission of the nodular lesions. Finally, a month later, she had complete resolution of the phlebitis, discontinuing heparin.
Keywords: thrombophlebitis, folliculitis, upper limb